Burger's medicinal chemistry, drug discovery and development. Volume 3 - Abraham, Donald J., 1936- (Hoboken, NJ : Wiley, 2021)
"Burger's is a flagship reference source for medicinal chemists and pharmaceutical professionals. This updated and expanded 8th edition has been thoroughly revised and improved to incorporate the concepts of drug hunting along with its existing coverage of the entire process of drug discovery and development. Bringing in a new and expert editorial board, this new edition updates existing chapters and adds 35 new ones, with topics including: opioid addiction treatments, antibody and gene therapy for cancer, blood-brain barrier, HIV treatments, and industrial-academic collaboration structures"--
volume 3. Drug development / volume editors, Ramnarayan S. Randad and Michael Myers
Revision of: Burger's medicinal chemistry and drug discovery. 6th ed. / edited by Donald J. Abraham. c2003.
Includes bibliographical references and index.
PHR
Keywords: Pharmaceutical chemistry; Drug development; Pharmacy